Targeting cancer stem cells with a pan-BCL-2 inhibitor in preclinical and clinical settings in patients with gastroesophageal carcinoma. Issue 12 (24th January 2021) - Song, Shumei; Chen, Qiongrong; Li, Yuan; Lei, Guang; Scott, Ailing; Huo, Longfei; Li, Cordelia Y; Estrella, Jeannelyn Santiano; Correa, Arlene; Pizzi, Melissa Pool; Ma, Lang; Jin, Jiankang; et al.
Abstract : Objective: Gastro-oesophageal cancers (GEC) are resistant to therapy and lead to poor prognosis. The cancer stem cells (CSCs) and antiapoptotic pathways often confer therapy resistance. We sought to elucidate the antitumour action of a BCL-2 inhibitor, AT101 in GEC in vitro, in vivo and in a clinical trial. Methods: Extensive preclinical studies in vitro and in vivo were carried out to establish the mechanism action of AT101 on targeting CSCs and antiapoptotic proteins. A pilot clinical trial in patients with GEC was completed with AT-101 added to standard chemoradiation. Results: Overexpression of BCL-2 and MCL-1 was noted in gastric cancer tissues (GC). AT-101 induced apoptosis, reduced proliferation and tumour sphere formation in MCL-1/BCL-2 high GC cells. Interestingly, AT101 dramatically downregulated genes ( YAP-1/Sox9 ) that control CSCs in GEC cell lines regardless of BCL-2/MCL-1 expression. Addition of docetaxel to AT-101 amplified its antiproliferation and induced apoptosis effects. In vivo studies confirmed the combination of AT101 and docetaxel demonstrated stronger antitumour activity accompanied with significant decrease of CSCs biomarkers (YAP1/SOX9). In a pilot clinical trial, 13 patients with oesophageal cancer (EC) received AT101 orally concurrently with chemoradiation. We observed dramatic clinical complete responses and encouraging overall survival in these patients. Clinical specimen analyses revealed that AT-101 dramatically reduced the expression of CSCs genes in treated EC specimens indicating antitumour activity of AT101 relies more on its anti-CSCs activity. Conclusions: Our preclinical and clinical data suggest that AT-101 overcomes resistance by targeting CSCs pathways suggesting a novel mechanism of action of AT101 in patients with GEC.